UUM saves RM500,000 without night classes - Ishak, Mohamed Mustafa (Daily Express (KK), 2011)
SINTOK: Universiti Utara Malaysia UUM saved up to RM500,000 without having night classes since early this year, Vice Chancellor Prof Datuk Dr Mohamed Mustafa Ishak said Thursday.